A Critical Analysis of the Book New Criticism of Story, Novel and Narrative in Arabic Literature - Payman Salehi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The great tendency of contemporary Arab fiction literature critics to new approaches of Western criticism, especially in the last decade of the twentieth century and concerns about the severance of their relationship with the old Arabic critique and the urgent need of Arab libraries for works on criticism of critiques, made the Syrian Abu Heif to write the book “New Criticism of Story, Novel and Narrative in Arabic Literature”. This research examined Abu Heif’s criticism method based on two methods of reading the work and descriptive-analytical approach and has reached the following results: The way the eight chapters of the book are presented in a very eloquent pen, illustrates that it has had a pre-determined engineering and the content topics have a logical and acceptable sequence. The data and examples in this book are vast; and in fact, Abu Heif has turned his book into an encyclopedia. Despite the fact that Abu Heif did not consider specific criticism criteria to criticize other critique works, and this is one of the main drawbacks of the book, his analysis of different critique works has a very solid base and is convincing for the reader. Citing of almost 500 works by critics from different Arab countries could be a strong reason for his lack of prejudice in using critical evidence.